The impact of implementing information technology governance based on the COBIT-2019 framework on institutional performance - AL-Qatanani, Khaled Mahmoud (Edelweiss Applied Science and Technology, 2025)
The objective of this study is to explore the impact of implementing Information Technology Governance (ITG) based on the ISACA [1] framework on institutional performance in Jordanian commercial banks. Specifically, the study examines the influence of the ISACA [1] framework: (Evaluate and Direct, acquiring, implementation, Service and Support) in institutional performance. IT governance (ITG) is a strategic and managerial process designed to ensure the effective and accountable use of information technology within an organization. The ISACA [1] framework is instrumental in improving the effectiveness of audit controls and processes, thereby enhancing the governance of IT operations. This research adopts a quantitative approach, utilizing a questionnaire to gather data from 160 participants, including audit managers, heads of audit departments, audit committee chairs, and auditors working in Jordanian commercial banks. Of the 160 questionnaires distributed, 152 were returned, 5 were excluded, and 148 valid responses were analysed. The results of the study indicate that all independent variables, including the ISACA [1] framework, have a positive and significant impact on institutional performance. One of the key findings of the research is that the "Monitor and Evaluate" dimension of IT governance has a particularly strong influence on institutional performance. This can be attributed to the essential role that IT delivery, along with the implementation of IT applications and services, plays in the functioning of organizational systems.